WASA’IL ITHBAT DALAM UNDANG-UNDANG KETERANGAN ISLAM: ANALISIS PERUNDANGAN TERHADAP KEABSAHAN DOKUMEN ELEKTRONIK DI MAHKAMAH SYARIAH MALAYSIA - Mohamad Aniq Aiman Alias; Wan Abdul Fattah Wan Ismail; Ahmad Syukran Baharuddin; Muzaffar Syah Mallow (Malaysian Journal of Syariah and Law)
In recent years, electronic documents have gained significant attention in legal proceedings, especially with the emergence of modern technology extensively utilized across various segments of society. Their convenient and rapid accessibility via electronic devices such as computers, smartphones, or tablets enables interested parties to obtain necessary information with ease. In Syariah courts, electronic documents serve as crucial evidence in either establishing an individual’s guilt or exonerating the innocent. Nonetheless, questions arise regarding the admissibility of such evidence under Syariah law in Malaysia and its function in trial proceedings. Therefore, this article aims to clarify the position of electronic document evidence in Malaysian Islamic evidence law by examining the concept of electronic documents as wasa’il ithbat, the relevant Islamic legal justifications (holy Quran, hadith and qawāʿid fiqhiyyah), and the statutory provisions applicable within the context of Islamic law of evidence in Malaysia. Several cases from Malaysian Syariah courts are analyzed to assess the validity of electronic evidence. The study further identifies challenges faced by Syariah legal practitioners and proposes measures to enhance the management of electronic evidence in the future. A qualitative method involving document analysis of both primary and secondary data was adopted to achieve the research objectives. Findings indicate that Malaysian Syariah courts do accept electronic documents as evidence in line with existing legal provisions and Islamic jurisprudence; however, issues concerning authenticity and reliability warrant closer attention. Accordingly, comprehensive guidelines, technological training for judges and court officers, and comparative studies with civil courts are recommended to reinforce the integrity and efficiency of electronic evidence management going forward.